Management of extracapsular condylar fracture with open reduction internal fixation in children: a case report - Putri, Puspita Rahardjo; Tauziri, Annisa Hasna Nurzahra; Kintara, Medinanisa; Sjamsudin, Endang; Oli’i, Eka Marwansyah (Dental Journal (Majalah Kedokteran Gigi), 2026)
Background: Mandibular condyle fracture is a fracture of the mandible that quite often occurs due to trauma. Complications that often ensue from condyle fractures in children are ankylosis and temporomandibular joint disorders. Mandibular fracture treatment can involve open reduction or closed reduction. Fracture treatment is simple and appropriate technique can prevent further complications. Purpose: The aim of this case report is to present the management of condylar fractures in pediatric patients resulting from trauma using the open reduction technique. Case: An eight-year-old female patient after experiencing a fall presented with complaints of not being able to open her mouth. Clinical and radiographic examination showed a type IIIb condyle fracture. Case management: The patient was then treated with the open reduction internal fixation (ORIF) technique. Two plates were installed in the patient’s left condylar area using a preauricular approach. The patient showed improved results on the 10th day of control. Conclusion: Treatment of mandibular condyle cases with the ORIF technique in children gives quite good results. Regular evaluation is needed.